2007
DOI: 10.1177/0146621606297314
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Adaptive Testing for Polytomous Motivation Items: Administration Mode Effects and a Comparison With Short Forms

Abstract: In a randomized experiment (n = 515), a computerized and a computerized adaptive test (CAT) are compared. The item pool consists of 24 polytomous motivation items. Although items are carefully selected, calibration data show that Samejima's graded response model did not fit the data optimally. A simulation study is done to assess possible consequences of model misfit. CAT efficiency was studied by a systematic comparison of the CAT with two types of conventional fixed length short forms, which are created to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…., k j items. Each fixed-length test was created by selecting the first i j administered items of the scale (see Hol et al, 2007, for a similar procedure).…”
Section: Methodsmentioning
confidence: 99%
“…., k j items. Each fixed-length test was created by selecting the first i j administered items of the scale (see Hol et al, 2007, for a similar procedure).…”
Section: Methodsmentioning
confidence: 99%
“…Computer adaptive testing methods shorten test length by 62.5%, or require only an estimated nine items (Hol et al, 2007). In the present study, our CAT used much fewer items than the preset ten items and average respondents answered slightly more than 6 items for each construct.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that CAT improves test efficiency maintaining adequate precision with fewer items than the full test (Elhan et al, 2008;Flynn et al, 2008;Haley et al, 2008;Hart et al, 2006;Hol et al, 2007;Jette et al, 2008;Velozo et al, 2006;Ware et al, 2003;Weiss, 1982). CAT measures are highly correlated with other assessments intending to measure the same construct and require fewer items.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have recently found that CAT improves both in measurement precision and efficiency relative to the full test (Elhan et al, 2008;Flynn et al, 2008;Haley et al, 2008;Hart et al, 2006;Hol et al, 2007;Jette et al, 2008;Ware et al, 2003;Weiss, 1982). Several studies have also been reported that CAT measures are highly correlated with other instruments measuring same construct and require fewer number of items with an average 6 items to reach the ability estimation (Fliege et al, 2009;Hart et al, 2008a;Hart et al, 2008b;Shone et al, 1993).…”
Section: Item Response Theory and Computer Adaptive Testingmentioning
confidence: 99%